2020
DOI: 10.1016/j.dcn.2020.100870
|View full text |Cite
|
Sign up to set email alerts
|

Adaptiveness in proactive control engagement in children and adults

Abstract: Highlights We examined efficiency of and adaptiveness in proactive control use as a function of contextual cue reliability in 6- and 9-year-olds and adults. All age groups showed greater behavioural, ERP and pupil dilation markers of proactive task selection when cues were reliable. Early developing use of contextual cue reliability ensures some degree of adaptiveness in proactive control engagement from 6 years onwards. Only adults addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…The present study thus provides additional evidence on children's emerging cognitive control skills by uncovering substantial and specific error monitoring skills. It appears that when the cognitive conflict is either predictable (in the Flower block, where all trials are equally conflicting) or not too complex (the Heart trials in the Mixed block), even 6-yearold children can adequately modulate their cognitive control, in this case here by specifically slowing down after an error Roebers 10.3389/fpsyg.2022.923615 (Ambrosi et al, 2016(Ambrosi et al, , 2019Chevalier et al, 2020;Niebaum et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study thus provides additional evidence on children's emerging cognitive control skills by uncovering substantial and specific error monitoring skills. It appears that when the cognitive conflict is either predictable (in the Flower block, where all trials are equally conflicting) or not too complex (the Heart trials in the Mixed block), even 6-yearold children can adequately modulate their cognitive control, in this case here by specifically slowing down after an error Roebers 10.3389/fpsyg.2022.923615 (Ambrosi et al, 2016(Ambrosi et al, , 2019Chevalier et al, 2020;Niebaum et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Proactive control in older children and adults is typically very efficient but also cognitively highly demanding ( Wright and Diamond, 2014 ; Kubota et al, 2020 ). Using different task paradigms, Chevalier and colleagues have accumulated evidence that developmental progression in cognitive control is—at least in part—due to an increased ability to control proactively ( Chevalier et al, 2020 ; Niebaum et al, 2020 ). This does not mean that 5- to 6-year-old children cannot engage in proactive control.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been demonstrated that working memory develop- pupil dilation (especially during the late-window) (e.g., Chevalier et al, 2015Chevalier et al, , 2020. In contrast, we can infer that children in the proactive training group engaged proactive control in the training phase where they were encouraged to use the cue to prepare for the target presentation, and continued to engage proactive control in the test phase where they were not encouraged to do so, resulting in no observed difference in response times and pupil dilation between the two phases.…”
Section: Discussionmentioning
confidence: 99%
“…In proactive-possible phases, the task cue appeared before the target, whereas it was presented on target onset in the proactive-impossible phase it is possible to use proactive control when cue contextual information always appears before target onset, and it is necessary to use proactive control when cue contextual information appears and then disappears before target onset (Chevalier et al, 2015). Furthermore, activating a task goal proactively is adaptive only when the task goal can be reliably predicted based on contextual cue information, thus it is also necessary to know about cue reliability in order to engaging proactive control efficiently (Chevalier et al, 2020). Therefore, as children become more knowledgeable about temporal structures of task environments and cue reliability, they can accumulate more task knowledge about the timing of task goal activation.…”
Section: Research Highlightsmentioning
confidence: 99%
“…That is, as children increasingly watch in anticipation of signals in the environment that are relevant to how they should act (such as a dog turning unfriendly or reaching a busy street), they improve in their abilities to stop themselves from behaving inappropriately. An extended developmental time course for proactive monitoring seems likely, given that early in development (3-5 years) children tend to engage control reactively at the moment as needed, and become more efficient and systematic in engaging control proactively, in advance of needing it, across the middle childhood years and beyond (Andrews-Hanna et al, 2011;Blackwell & Munakata, 2014;Chatham, Frank, & Munakata, 2009;Chevalier, Martis, Curran, & Munakata, 2015;Chevalier, Meaney, Traut, & Munakata, 2020;Lucenet & Blaye, 2014;Vallesi & Shallice, 2007;Waxer & Morton, 2011). This developmental shift in the temporal dynamics of control highlights that limitations in proactive monitoring may contribute to limitations in children's response inhibition.…”
mentioning
confidence: 99%